About the textbook “Lithological and reservoir properties of sedimentary rocks” - S. A. Samokhvalov; V. N. Komarov (Известия высших учебных заведений: Геология и разведка)
The textbook2 under review examines relationships between the lithological features of sand-siltstone and carbonate reservoir rocks and their petrophysical properties. The reservoir properties of rocks depend on their lithological characteristics, being their function. As part of petrophysicalresearch works, specific features in the lithological study of reservoir rocks are determined, their main lithological and petrophysical properties are characterized, and the sequence of their study is considered. The textbook provides numerous examples confirming the unambiguity or ambiguityof lithological and petrographic relationships identified by other researchers in the study of reservoirs of different ages. The textbook is based on the original material obtained by the authors when studying the oil and gas provinces of the Russian Federation.